Let
A = ∫ 0 1 sin 6 x + cos 6 x 1 d x
Submit ⌊ 1 0 0 0 0 A ⌋ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A = ∫ 0 1 sin 6 x + cos 6 x 1 d x = ∫ 0 1 ( sin 2 x + cos 2 x ) ( ( sin 2 x + cos 2 x ) 2 − 3 sin 2 x cos 2 x ) 1 d x = ∫ 0 1 1 − 3 sin 2 x cos 2 x 1 d x = ∫ 0 1 sec 4 x − 3 tan 2 x sec 4 x d x = ∫ 0 1 ( 1 + tan 2 x ) 2 − 3 tan 2 x ( 1 + tan 2 x ) sec 2 x d x = ∫ 0 tan 1 ( 1 + t 2 ) 2 − 3 t 2 1 + t 2 d t = ∫ 0 tan 1 ( t 2 − 3 t + 1 ) ( t 2 + 3 t + 1 ) t 2 + 1 d t = ∫ 0 tan 1 2 1 ( t 2 − 3 t + 1 1 + t 2 + 3 t + 1 1 ) d t = ∫ 0 tan 1 2 1 ⎝ ⎜ ⎛ ( t − 2 3 ) 2 + 4 1 1 + ( t + 2 3 ) 2 + 4 1 1 ⎠ ⎟ ⎞ d t = ∫ 0 tan 1 ( ( 2 t − 3 ) 2 + 1 2 + ( 2 t + 3 ) 2 + 1 2 ) d t = tan − 1 ( 2 t − 3 ) + tan − 1 ( 2 t + 3 ) ∣ ∣ ∣ ∣ 0 tan 1 = tan − 1 ( 2 tan 1 − 3 ) + 3 π + tan − 1 ( 2 tan 1 + 3 ) − 3 π = tan − 1 ( 3 + 2 tan 1 ) − tan − 1 ( 3 − 2 tan 1 ) ≈ 2 . 3 1 2 0 0 Note that a 3 + b 3 = ( a + b ) ( a 2 + b 2 − a b ) = ( a + b ) ( ( a + b ) 2 − 2 a b ) Multiply up and down by sec 4 x . Let t = tan x ⟹ d t = sec 2 x d x By partial fraction decomposition
Therefore ⌊ 1 0 0 0 0 A ⌋ = 2 3 1 2 0 .
Small typo on line 2 : sin^x
Problem Loading...
Note Loading...
Set Loading...
∫ 0 1 sin 6 x + cos 6 x 1 d x = ∫ 0 1 1 − 3 sin 2 x cos 2 x 1 d x Taking 2 x = u , = ∫ 0 1 4 − 3 sin 2 ( 2 x ) 4 d x = ∫ 0 2 4 − 3 sin 2 u 2 d u The integral is same as ∫ 0 2 4 cos 2 u + sin 2 u 2 d u = 2 ∫ 0 2 4 cot 2 u + 1 cosec 2 u d u taking c o t u = t the integral becomes ,
= − 2 1 ∫ ∞ cot ( 2 ) t 2 + 4 1 d t = [ − tan − 1 ( 2 t ) ] ∞ cot 2 ⟹ 2 π − tan − 1 ( 2 cot 2 ) Answer is [ 1 0 0 0 0 × ( 2 π − tan − 1 ( 2 cot 2 ) ) ] = 2 3 1 2 0